Educational play and its reflection on the psychosocial compatibility of a preschool child (3-5) years in Algiers - Hachemane, Abdenour (Journal of Human Sciences, 2021)
Psychosocial compatibility is a recent topic adopted by social sciences, where this study deals with the effect of play on the psychosocial compatibility of a preschool child, by addressing the reflection of educational play on psychological and social compatibility as a whole, and whether it contributes to directing and controlling his emotional development. The children's personality test and the questionnaire were adopted, as for the statistical tools; the percentage, the arithmetic mean, the standard deviation, and the t-test were used. Among the most important results that have been reached is that educational play in kindergarten has a role in achieving a balanced psychological and social harmony for the child, and that the educator has a role in achieving this compatibility through her competence and knowledge of the methods of educational play and directing it towards achieving it.